(untitled) (Colloquia Comparativa Litterarum, 2025)
This article examines how women writers in the Balkans from the second half of the 20th century narrate war. The focus of the study is on the museum’s classifying function to include narrative forms such as the album and the diary, in the genre of the novel. In order to narrate a major theme like the war, Dubravka Ugrešić (Croatia) and Blaga Dimitrova (Bulgaria) use these two forms, traditionally thought to be representative of the female voice. The study traces the literary and museum representations of the album and the diary in which memory plays the major role.